Indications for reoperation after sleeve gastrectomy - Doğan, Fadlı; Dincer, Mürşit (My University, 2019)
Introduction: Morbid obesity is a serious health condition. Surgical interventions play an essential role in treatment, and sleeve gastrectomy is one of the most widely performed bariatric surgical procedures. After bariatric surgery, some patients may require reoperation for several reasons, such as complications, cholelithiasis, and gastroesophageal reflux. This study is an examination of the indications for reoperationand the results observed in patients who underwent reoperation following sleeve gastrectomy.Materials and Methods: Patients who were reoperated on after sleeve gastrectomy for various reasons were analyzed retrospectively. The demographic characteristics, reoperation indications, surgical procedures, and results were analyzed.Results: Of a total of 1268 patients who underwent sleeve gastrectomy due to obesity, 15 who had a reoperation after laparoscopic sleeve gastrectomy were included in the study. The overall reoperation rate after sleeve gastrectomy was 1.18%. Cholelithiasis leak, hemorrhage, stenosis, intra-abdominal hematoma, and incisional hernia were identifid as indications for reoperation.Conclusion: Reoperation for the patients who undergo bariatric surgery may be required for a number of reasons. The results of this study indicate that a second procedure after sleeve gastrectomy can be performedsafely and with minimal risk.
Keywords: Cerrahi